Factors affecting Teaching Competency of Academic Staff, - K.T. Lahariya; P.O. lngle (Journal of Agricultural Extension Management, 2025)
Teaching competency can be evaluated in terms of the student’s achievement and attitude as the product criterion. Good teaching is the main criterion of a competent teacher. The competent teacher never stops experimenting to discover what best suits his own particular needs and those of his students. The competent teacher can apply teaching methods that are easier, quicker, better, safer, more rewarding, less labour intensive and more suitable